Hidden Agenda - The Involvement of Endoplasmic Reticulum Stress and Unfolded Protein Response in Inflammation-Induced Muscle Wasting - Kny, Melanie; Fielitz, Jens (Frontiers in Immunology, 2022)
Critically ill patients at the intensive care unit (ICU) often develop a generalized weakness, called ICU-acquired weakness (ICUAW). A major contributor to ICUAW is muscle atrophy, a loss of skeletal muscle mass and function. Skeletal muscle assures almost all of the vital functions of our body. It adapts rapidly in response to physiological as well as pathological stress, such as inactivity, immobilization, and inflammation. In response to a reduced workload or inflammation muscle atrophy develops. Recent work suggests that adaptive or maladaptive processes in the endoplasmic reticulum (ER), also known as sarcoplasmic reticulum, contributes to this process. In muscle cells, the ER is a highly specialized cellular organelle that assures calcium homeostasis and therefore muscle contraction. The ER also assures correct folding of proteins that are secreted or localized to the cell membrane. Protein folding is a highly error prone process and accumulation of misfolded or unfolded proteins can cause ER stress, which is counteracted by the activation of a signaling network known as the unfolded protein response (UPR). Three ER membrane residing molecules, protein kinase R-like endoplasmic reticulum kinase (PERK), inositol requiring protein 1a (IRE1a), and activating transcription factor 6 (ATF6) initiate the UPR. The UPR aims to restore ER homeostasis by reducing overall protein synthesis and increasing gene expression of various ER chaperone proteins. If ER stress persists or cannot be resolved cell death pathways are activated. Although, ER stress-induced UPR pathways are known to be important for regulation of skeletal muscle mass and function as well as for inflammation and immune response its function in ICUAW is still elusive. Given recent advances in the development of ER stress modifying molecules for neurodegenerative diseases and cancer, it is important to know whether or not therapeutic interventions in ER stress pathways have favorable effects and these compounds can be used to prevent or treat ICUAW. In this review, we focus on the role of ER stress-induced UPR in skeletal muscle during critical illness and in response to predisposing risk factors such as immobilization, starvation and inflammation as well as ICUAW treatment to foster research for this devastating clinical problem.